Symbiotic simulation for decision support in high-tech manufacturing and service networks - Zeng, Fanchao (2009)
With the increasing growth of manufacture networks as well as the global competitions in the lubricant industry, the management of supply chain is vital for large vertically-integrated petroleum companies. Operational decision-making should consider the entire supply chain which includes upstream raw material suppliers, downstream customers as well as the internal entities of the specialty chemicals company.